Five Neurology Cases for Third-Year OSCEs - Khadeja Johnson; Janice Hall; Roger Simon; Kitty Carter-Wicker; Makia Powers; Martha Elks (Association of American Medical Colleges, 2016)
Abstract The use of standardized patients (SPs) in an objective structured clinical examination (OSCE) format is well documented as a successful means of training students in the basics of clinical skills since it provides a rehearsal for students to practice in a safe environment. These five neurological-based SP cases were developed at the Morehouse School of Medicine. They include cluster headache, multiple sclerosis, neurologic exam for preemployment, Parkinson disease, and lateral femoral cutaneous nerve entrapment. All five cases were constructed to be all summative, all formative, and/or a combination of both types of assessments depending on the availability of faculty preceptors for direct feedback. In addition, most cases were written such that slight modifications could easily accommodate an SP of the opposite gender. The Morehouse School of Medicine has used these neurology cases for over 2 years. The first year, the five neurology cases were used as a summative OSCE. The following years, we made two of the cases direct feedback for formative evaluation. The learners appreciated the direct feedback much more than a pure summative assessment. The limitation with having a formative was that faculty members had to be available at each OSCE in order to provide the direct feedback. Future plans include implementing evaluations to gather data demonstrating impact of the OSCE (i.e., if the learners' comfort levels have increased as pertains to the neurological exams). Also, OSCE evaluations from learners, SPs, and/or preceptors could help correct deficiencies in any portion of the process. We feel that the use of SPs in the OSCE setting has translated to increased diagnostic and physical examination acumen in real practice with neurological patients. However, this is our perception and is not yet supported by data.